The incidence of insect pests on potato crop in Hazara division, Khyber Pakhtunkhwa, Pakistan - Ghalib Sayyid; Zahid Khan; Haroon, et al. (Arthropods)
The research was conducted on insect pests in Hazara division (Mansehra, Abbottabad, Battagram, Haripur, Kohistan, and Tor Ghar) on potato crops under the proposed project. From each district, five fields were selected and major and minor insect pests were collected on potato during the visit. The preserved insects were identified in NARC, and the reported species in 5-meter row were as follows: leafhopper, 0.53±0.40, 0.46±0.26, 0.40±0.17, 0.34±0.15 and 0.32±0.20; flea beetle, 0.58±0.39, 0.57±0.55, 0.33±0.16, 0.45±0.4 and 0.27±0.18; potato tuberworm, 0.68±0.44, 0.65±.60, 0.55±0.52, 0.40±0.28, and 0.28±0.18; black cutworm, 0.60±0.29, 0.58±0.54, 0.33±0.18, 0.32±0.20 and 0.47±0.34; wireworm, 0.62±0.35, 0.55±0.50, 0.53±0.31, 0.50±0.27 and 0.35±0.21; white grub, 0.55±0.33, 0.60±0.53, 0.38±0.26, 0.80±0.60 and 1.14±1.19. The seasonal average of each insect in each district was different in incidence. The difference in the pest population in different districts of the Hazara division is due to the climate conditions, temperature, and incidence of pests.